Compact Low Weight High Gain Broadband Antenna by Polarization-Rotation Technique for X-Band Radar - Amir Reza Dastkhosh; Hamidreza Dalili Oskouei; Gholamreza Khademevatan (International Journal of Antennas and Propagation)
Less efficiency and gain is achieved by existence of aperture blocking phenomena in cassegrain antenna caused by the presence of subreflector or antenna feed. Also, length of feed cables causes delay which is another undesirable problem in antennas, since errors and less precision of detecting targets are created. To overcome these problems, low weight and compact optimized polarization-rotation monopulse cassegrain antenna is designed in this paper. The goal of our proposed rotating antenna is achievement of sum and difference patterns for target tracking in monopulse radar. In our work, left part of hyperbolic subreflector instead of right one has been used for reducing size of the antenna. The antenna is fabricated by grid wires instead of solid sheet metal reflectors and with composite technology for decreasing its weight. Width and volume of the antenna reduce by about 50% in comparison to other reflector antennas. This antenna has been simulated and manufactured in X-band and simulation data are in good agreement with measured ones. The antenna has the average gain of 35 dB from 8.5 up to 9.5 GHz. Also the antenna feed bandwidth is more than 50% and the antenna has efficiency of about 50% from 8 up to 10 GHz.